Geographical and Seasonal Thermal Sensitivity of Grazing Pressure by Microzooplankton in Contrasting Marine Ecosystems - Cabrerizo, Marco J.; Marañón, Emilio (Frontiers in Microbiology, 2021)
Grazing pressure, estimated as the ratio between microzooplankton grazing and phytoplankton growth rates (g:µ), is a strong determinant of microbial food-web structure and element cycling in the upper ocean. It is generally accepted that g is more sensitive to temperature than µ, but it remains unknown how the thermal dependence (activation energy, Ea) of g:µ varies over spatial and temporal scales. To tackle this uncertainty, we used an extensive literature analysis obtaining 751 paired rates estimates of µ and g from dilution experiments performed in different biomes and oceanic areas. On a geographical scale, we found a stimulatory effect of temperature in polar open-ocean ( 0.5 eV) and tropical coastal ( 0.2 eV) ecosystems, and an inhibitory one in the remaining biomes/ecosystems (values between -0.1 and -0.4 eV). On a seasonal scale, the temperature effect on g:µ ratios was stimulatory, particularly in polar environments; however, the large variability existing between estimates resulted in non significant differences among biomes. We observed that increases in nitrate availability stimulated the temperature dependence of grazing pressure (i.e. led to more positive Ea of g:µ) in open-ocean ecosystems and inhibited it in coastal ones, particularly in polar environments. Despite these contrasting patterns in thermal sensitivity of grazing pressure, the percentage of primary production grazed by microzooplankton ( 56%) was similar in all ocean areas. These findings suggest that on-going warming of surface ocean waters could exert a variable impact, in terms of both magnitude and direction (stimulation or inhibition), on microzooplankton grazing pressure in different ocean regions.